1979
DOI: 10.1007/bf02294701
|View full text |Cite
|
Sign up to set email alerts
|

On the base-free measure of change proposed by Tucker, Damarin and Messick

Abstract: base-free measure of change, difference scores, measuring change,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…To adjust for baseline variance, residualized values were created using a linear regression of follow-up on baseline values. Residualized values are referred to as “baseline-free” measures of change that help combat “regression to the mean” in change analyes [ 36 , 37 , 38 ]. There were two steps in creating change groups.…”
Section: Methodsmentioning
confidence: 99%
“…To adjust for baseline variance, residualized values were created using a linear regression of follow-up on baseline values. Residualized values are referred to as “baseline-free” measures of change that help combat “regression to the mean” in change analyes [ 36 , 37 , 38 ]. There were two steps in creating change groups.…”
Section: Methodsmentioning
confidence: 99%
“…Standardized tests are increasingly used to calculate gain scores in an effort to measure student learning and evaluate teacher performance. Prior research has examined the reliability of measures of growth and change (e.g., Bond, 1979; Cronbach & Furby, 1970; Tucker, Damarin, & Messick, 1966; Zimmerman & Williams, 1998). Some special cases of a broader class of linear gain scores (LGS) have become popular measures of student learning as researchers and decision makers attempt to quantitatively evaluate the impact of teachers on students (Battauz, Bellio, & Gori, 2011; Lockwood, McCaffrey, Mariano, & Setodji, 2007; McCaffrey, Lockwood, Koretz, Louis, & Hamilton, 2004; Woodhouse, Yang, Goldstein, & Rasbash, 1996).…”
mentioning
confidence: 99%
“…Educational Testing Service Bond (1979) pointed out a presumably incorrect derivation in the Tucker, Damarin, and Messick (1966) presentation of a base-free measure of change. As a consequence, Bond argued that properties attributed to a (the coefficient for the regression of true scores from the second testing on true scores from the first testing) were instead properties of b, the corresponding regression coefficient for observed scores.…”
mentioning
confidence: 99%
“…Using the Tucker et al (1966) notation which was also followed by Bond (1979), as well as standard relationships from classical test theory, the basefree measure of change (y) is defined as a true independent change score: Tucker et al (1966) and formula (14) in Bond (1979) give the correlation between an observed difference score and any other variable k, one to determine the difference score and one to correlate with the difference score, eliminates the negative bias in P d produced by correlated errors Xl (Thorndike, 1966), Equation (4) then becomes, with inserts from equation (3), (6) is algebraically equivalent to equation (63) in Tucker et al (1966), which gives the correlation between observed initial position and the observed difference score corrected for correlated errors. It is clear from equation (6) that PX'd is positive when a > 1, is zero when a = 1, and is negative when a < 1.…”
mentioning
confidence: 99%